2002
DOI: 10.1038/sj/jim/7000190
|View full text |Cite
|
Sign up to set email alerts
|

Halocins and sulfolobicins: The emerging story of archaeal protein and peptide antibiotics

Abstract: Production of antibiotic peptides and proteins is a near-universal feature of living organisms regardless of phylogenetic classification. Bacteriocins (proteinaceous antimicrobials from the domain Bacteria) have been studied for over 75 years, and the eucaryocins (proteinaceous antimicrobials from the domain Eucarya) since the early 1960s. However, one domain of organisms, the Archaea, containing hyperthermophiles, extreme halophiles and the methanogens, is just beginning to be scrutinized for the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 50 publications
0
72
0
Order By: Relevance
“…Culture-independent surveys have shown them to be present in virtually every natural habitat (5). Archaea produce so-called archaeocins, but until now only a few of these antimicrobial (poly)peptides have been described (14,16,17). Halocins are archaeocins that are produced by halophilic euryarchaea (13).…”
mentioning
confidence: 99%
“…Culture-independent surveys have shown them to be present in virtually every natural habitat (5). Archaea produce so-called archaeocins, but until now only a few of these antimicrobial (poly)peptides have been described (14,16,17). Halocins are archaeocins that are produced by halophilic euryarchaea (13).…”
mentioning
confidence: 99%
“…Reported that halocin activity reached a maximum during the transition to stationary phase at the end of the exponential growth phase and then decreased to low levels, and reasoned this might be due to the rapid increase in gene expression level in the late stationary phase. Among the halocins investigated so far most of them are first detectable when culture of the producing cells enters the stationary growth phase (Shand et al, 1999 andShand, 2002 He et al (2006) reported that the maximum antagonistic activity was found in the precipitate obtained with 60% saturation of ammonium sulfate for the cell-free supernatant of Bacillus licheniformis. In the present attempt it was 70%.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…O"Connor and Shand (2002) reported the microhalicins with molecular weight of 3.6kDa and 3.8kDa from the Halobacterium sp. whereas Sun et al (2005) reported slightly larger purified compound of 7.44 kDa.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…Additionally, a relatively small number of bacteriocins from Archaeal species have also been characterized. A comprehensive review of bacteriocins from Bacteria and Archaea can be found elsewhere (O'Connor & Shand, 2002;Reeves, 1965;Riley & Gordon, 1999;Riley & Wertz, 2002a, 2002bTagg et al, 1976). Below are short descriptions of the bacteriocin classes of Bacteria and Archaea and examples of bacteriocins belonging to each class ( …”
Section: Bacteriocin Classesmentioning
confidence: 99%